Long non-coding RNA NMRAL2P promotes glycolysis and reduces ROS in head and neck tumors by interacting with the ENO1 protein and promoting GPX2 transcription - Nie, Qian; Cao, Huan; Yang, JianWang; Liu, Tao; Wang, BaoShan (PeerJ, 2023)
Background Metabolic reprogramming is a key marker in the occurrence and development of tumors. This process generates more reactive oxygen species (ROS), promoting the development of oxidative stress. To prevent ROS from harming tumor cells, tumor cells can increase the production of reducing agents to counteract excessive ROS. NMRAL2P has been shown to promote the production of reductive mRNA and plays an important role in the process of oxidative stress. Methods In this study, the clinical data and RNA sequencing of head and neck tumors were obtained from The Cancer Genome Atlas data set. The long non-coding RNA (LncRNA) related to oxidative stress were then identified using differential and correlation analyses. The differential expression and prognosis of the identified lncRNA were then verified using samples from the library of the Second Hospital of Hebei Medical University. Only NMRAL2P was substantially expressed in cancer tissues and predicted a poor prognosis. The tumor-promoting impact of NMRAL2P was then confirmed using in vitro functional assays. The data set was then split into high- and low-expression subgroups based on the median gene expression of NMRAL2P to obtain the mRNA that had a large difference between the two groups, and examine the mechanism of NMRAL2P on GPX2 using quantitative real-time PCR, RNA binding protein immunoprecipitation assay, and chromatin immunoprecipitation. Mass spectrometry was used to identify NMRAL2P-binding proteins and western blotting was used to investigate probable mechanisms. Results The lncRNA NMRAL2P is associated with oxidative stress in head and neck tumors. In vitro functional assays showed that the gene has a cancer-promoting effect, increasing lactic acid and superoxide dismutase production, and reducing the production of ROS and malondialdehyde. NMRAL2P promotes the transcription of GPX2 by binding to transcription factor Nrf2. The gene also inhibits the degradation of ENO1, a crucial enzyme in glycolysis, by binding to protein ENO1. Conclusions This study shows that NMRAL2P can promote glycolysis and reduce the harm to tumor cells caused by ROS. The gene can also be used as a possible target for the treatment of head and neck tumors.
Keywords: NMRAL2P; GPX2; ENO1; Glycolysis; ROS